The Second Sodium Site in the Dopamine Transporter Controls Cation Permeation and Is Regulated by Chloride - Borre, Lars (American Society for Biochemistry and Molecular Biology, 2014)
The dopamine transporter (DAT) belongs to the family of neurotransmitter:sodium symporters and controls dopamine (DA) homeostasis by mediating Na(+)- and Cl(−)-dependent reuptake of DA. Here we used two-electrode voltage clamp measurements in Xenopus oocytes together with targeted mutagenesis to investigate the mechanistic relationship between DAT ion binding sites and transporter conductances. In Li(+), DAT displayed a cocaine-sensitive cation leak current ∼10-fold larger than the substrate-induced current in Na(+). Mutation of Na(+) coordinating residues in the first (Na1) and second (Na2) binding sites suggested that the Li(+) leak depends on Li(+) interaction with Na2 rather than Na1. DA caused a marked inhibition of the Li(+) leak, consistent with the ability of the substrate to interact with the Li(+)-occupied state of the transporter. The leak current in Li(+) was also potently inhibited by low millimolar concentrations of Na(+), which according to our mutational data conceivably depended on high affinity binding to Na1. The Li(+) leak was further regulated by Cl(−) that most likely increases Li(+) permeation by allosterically lowering Na2 affinity. Interestingly, mutational lowering of Na2 affinity by substituting Asp-420 with asparagine dramatically increased cation permeability in Na(+) to a level higher than seen in Li(+). In addition to reveal a functional link between the bound Cl(−) and the cation bound in the Na2 site, the data support a key role of Na2 in determining cation permeability of the transporter and thereby possibly in regulating the opening probability of the inner gate.